The Interplay of Islamic History and Modern Quranic Hermeneutics Fadel Al-Rubaie and Khazal Al-Majdi: Two Case Studies - Dr. Natiq Najm Abdullah (Journal of College of Education, 2025)
This study discusses the possibilities of methodological integration between historical studies—particularly those related to ancient history, ethnography, and civilizations—and contemporary readings of the Qur’anic text. It adopts the works of the two Iraqi researchers Fadhil Al-Rubaie and Khazal Al-Majidi as applied case studies. The paper reviews their respective methodologies, identifies points of convergence and divergence with traditional and contemporary Qur’anic exegetical approaches, and proposes a methodological framework for incorporating historical and critical findings into modern Qur’anic interpretations in a manner that preserves the integrity of the text and its capacity for scholarly inference.
Keywords: Islamic History; Contemporary Readings; Fadhil Al-Rubaie; Khazal Al-Majidi